1976
DOI: 10.1037/0022-3514.34.5.930
|View full text |Cite
|
Sign up to set email alerts
|

Order of consensus, distinctiveness, and consistency information and causal attributions.

Abstract: In two studies, we examined the hypothesis that the order of presenting consensus, distinctiveness, and consistency information concerning an event may affect attributions of causality for the event. In particular, it seemed possible that the relative weakness of consensus information in previous studies may have been due, in part, to a recency effect because consensus was always presented first. Undergraduate subjects, assigned to one of several order conditions, were given questionnaires containing descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
1
1

Year Published

1977
1977
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 13 publications
(22 reference statements)
5
49
1
1
Order By: Relevance
“…Each interaction was demonstrated directly, and we followed the lead of researchers who focused only on one cue (e.g., Rholes & Ruble, 1984; Ruble et al., 1979) rather than all three attributional cues at once. The latter design feature eliminated the possibility of the other cues overshadowing consensus (see Ruble & Feldman, 1976). Yet, participants largely disregarded the cue.…”
Section: Discussionmentioning
confidence: 99%
“…Each interaction was demonstrated directly, and we followed the lead of researchers who focused only on one cue (e.g., Rholes & Ruble, 1984; Ruble et al., 1979) rather than all three attributional cues at once. The latter design feature eliminated the possibility of the other cues overshadowing consensus (see Ruble & Feldman, 1976). Yet, participants largely disregarded the cue.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent papers indicate that apart from matters of logic, attributional processes may be importantly affected by superficial manipulations that affect the perceptual salience of information. For example, Ruble and Feldman (1976) showed that consensus data was utilized most effectively when it was presented last in the sequence of &dquo;background material&dquo; associated with a given action. They suggest that earlier investigators (tiacarthur.…”
Section: Attribution Theorymentioning
confidence: 98%
“…McArthur found that all three information variables were used by subjects in this task, with the distinctiveness variable having the greatest effect overall (consistency in turn outweighed consensus). A study by Ruble and Feldman (1976) replicated the overall effect of McArthur's study, but when it randomized the order of the three information variables (something McArthur had patently failed to do), it did not find such a consistent pattern for the ordering in terms of importance of the three variables. Nevertheless, the McArthur and Ruble and Feldman studies represent one kind of explicit test of the model.…”
Section: Introductionmentioning
confidence: 62%